The Rationale for the Duty to Consult Indigenous Peoples: Comparative Reflections from Nordic and Canadian Legal Contexts - Christina Allard (Arctic Review on Law and Politics, 2018)
Although the standard of consulting Indigenous peoples in decisions affecting them is well rooted internationally as well as in national legal systems, different views and patterns of problems are associated with the concept and its practice. This paper briefly analyses and contrasts the duty to consult Indigenous peoples through a comparison of the three Nordic countries Norway, Finland and Sweden, and Canada. Based on domestic legal sources, the focus of the paper is to explore the legal foundation that has given rise to the specific set of rules for the duty to consult, that is, the rationale behind the evolving of the rules. The first finding is that the rules differ among the three Nordic countries, with Sweden being the only country that lacks specific rules. Secondly, whereas Canada has developed its own duty to consult primarily through domestic case law, in the Nordic countries, duty to consult is related to international law obligations. Consultation duties that have evolved from domestic law may be easier to accept than “foreign” regulations imposed on national legal systems. This could explain the reluctance among the Nordic States to accept specific consultations with the Sami Parliament and other Sami groups, particularly in Sweden.